Analytical Performance Comparison of IoT Communication Protocols MQTT and CoAP from Security Perspective - Swain, Satyaprakash; Pattanayak, Binod Kumar; Mohanty, Mihir Narayan; Senapati, Chinmayee (2024 3rd Odisha International Conference on Electrical Power Engineering, Communication and Computing Technology (ODICON), 2024)
In this present scenario, world Internet is maximum based on H2H communication only. But in the principle of IoT, it reduces direct Human-Human and Human-Machine communication. IoT provides support to work 24 X 7 over the year without affecting the accuracy of result. IoT environment is fully based on sensors and actuators. Sensor is responsible for data collection as well as for the route of transmission and actuator is responsible for security of data, communication of data and for accuracy of data. From application point of view, now days all critical sectors like: health care sectors, defense sectors, Aviation sectors, Space sectors are strictly working on the application of IoT. Most of the work is there performed by their automated systems. If any error occurs at the time of data transmission, then that may cause a serious loss for the society. So, security mechanism is most vital part for all IoT systems. Though IoT is based on machine-to-machine communications without human intervention, we need to emphasize both on device structures and their protocols. Generally, IoT devices are very small in size and its embedded applications are less complexity. We need maximum attention if any modification is carried out in its structure. There are various types of IoT protocols available, out of them two most common protocols are CoAP and MQTT. Different security algorithms are used by these protocols for encryption and decryption of these data. Two most security algorithms are AES and ECC algorithm. The algorithm which takes low time for key generation is most suitable for IoT protocols. In this research, we are going to find out different Lou points of these two protocols. Then we will analyze two most common security algorithms i.e. AES and ECC key generation time using python codes and we will compare these times to its hybrid model key generation time. At last we have proposed a new security algorithm i.e. AES-ECC hybrid algorithm for IoT communication protocols.